Multiphase Flow Analysis of Three-Dimensional Journal Bearing with Roughness Using Computational Fluid Dynamics (CFD) - S Susilowati; Silvana Dwi Nurherdiana; Sukirmiyadi; Erwan Adi Saputro; Mohammad Tauviqirrahman; Dani Arfiandani; Paryanto (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Investigating the impact of surface roughness characteristics on three-dimensional journal bearings while adjusting the eccentricity ratio is the primary goal of this work. Based on computational fluid dynamics, the rotor-bearing system with sand-grain roughness distribution surface is investigated (CFD). To study the tribological performance, the Reynolds-Average Navier-Stokes equations are combined with a multi-phase cavitation model (hydrodynamic pressure, load support and friction). The calculation demonstrates that the surface roughness level in relation to friction and load support is a determining factor for journal bearing performance